2012
DOI: 10.2165/11631530-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Extended-Release Niacin/Laropiprant Effects on Lp(a), ApoB, non-HDL-C, Apo A1, and ApoB/ApoA1 Ratio Across Patient Subgroups

Abstract: Registered as Clinicaltrials.gov NCT00269204, NCT00269217, NCT00479388, and NCT00485758.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…63,67 In one study of initially healthy women, extremely high levels of Lp(a) ($90th percentile) were associated with increased cardiovascular risk, particularly in women with high levels of low-density lipoprotein cholesterol. 70,71 There are some small studies that suggest that apheresis can help reduce levels also. 68 On the other hand, in African Americans, who have been shown to generally have higher Lp(a) levels, the data is more conflicting.…”
Section: Lipoprotein (A)mentioning
confidence: 99%
“…63,67 In one study of initially healthy women, extremely high levels of Lp(a) ($90th percentile) were associated with increased cardiovascular risk, particularly in women with high levels of low-density lipoprotein cholesterol. 70,71 There are some small studies that suggest that apheresis can help reduce levels also. 68 On the other hand, in African Americans, who have been shown to generally have higher Lp(a) levels, the data is more conflicting.…”
Section: Lipoprotein (A)mentioning
confidence: 99%
“…The combination of niacin/laropiprant plus a statin compared with doubling of the statin dose showed that combination treatment was associated with a significantly greater decrease in TG and LDL-C and a significantly greater increase in HDL-C [9]. An analysis of 4 trials of niacin/laropiprant revealed that this combination led to significantly larger decreases in TG, LDL-C, non-HDL-C, apoB, and Lp(a) and significantly greater increases in HDL-C and apoA-I compared with placebo or active comparator [10]. …”
Section: Niacin and Niacin Receptor Agonistsmentioning
confidence: 99%
“…Unfortunately, robust elevations of apoA‐I have been difficult to achieve by pharmacotherapy. Fibrates and niacin typically achieve <10% elevation, while dalcetrapib and torcetrapib achieved only 10% to 25% elevation . Additionally, the predominant change caused by these agents is an increase in HDL particle size, and larger HDL particles do not efficiently interact with the ABCA1 transporter …”
Section: Introductionmentioning
confidence: 99%